PEMERINTAH DAERAH SEBAGAI AKTOR DIPLOMASI: PERAN PEMERINTAH DAERAH KALIMANTAN BARAT DALAM MENANGANI PENYELUNDUPAN TKI ILEGAL DI PERBATASAN ENTIKONG - Aisyah Sari Pratiwi; Hermini Susitianingsih; Nadia Farabi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
The transformation of economic opportunities in Indonesia from agriculturalto industrial sector, causes rural communities lost their opportunity towork. Industrial sector needs well-educated workers, while rural communitiescan not compete because they have poor education. That is why ruralcommunities prefer to work abroad and become Indonesian migrant workers(TKI). Different types of problem always follow ever since their departure tohost countries. One of the problem is improper procedure or illegal migrant.One of case studies that depict this situation is migrant workers smuggling inthe border area of Entikong, West Kalimantan. The purpose of this researchis to examine the role of West Kalimantan Government in terms of addressingand handling the illegal migrants smuggling at the border area ofEntikong. This research employs concepts such as paradiplomacy,transnational crimes and international cooperation. The method used isqualitative using descriptive analysis through literature studies and deepinterviews. This research finds that the role of West Kalimantan Governmentas an actor of international relations by implementing previous centralgovernment policies as result of the cooperation between Indonesia andMalaysia. The local government has been conducting various strategiesranging from deportation to repatriation of the Indonesian illegal migrants.